The relationship between talent management and talent engagement: evidence from a telecommunications service provider in Malaysia / Anika Nadine Sedlacek - Sedlacek, Anika Nadine (2019)
Talent management in organisations is often considered as a necessity to be well-equipped for the fight in the ongoing war for talent and its importance even seems to increase with regard to the predicted talent shortage, affecting various countries in the next years. A Malaysian telecommunications service provider implemented talent management in its organisation in 2008. Until today, the outcome of its talent management, whether it has any effect on its organisational performance, has never been investigated. Accordingly, this study aims at determining the relationship between the organisation’s talent management and its talents’ engagement and thereby, aims at confirming or disproving the prevailing opinion of a positive relationship between the two variables. Hereby, it is assumed that talent management has direct impact on talent engagement and also on the talents’ abilities, motivation and opportunities at work, which then again influence the talents’ engagement positively. The study is mainly based on data obtained from a survey among the talents of the investigated telecommunications company, which polled the talents’ perceptions of the talent management practices as well as their ability, motivation, opportunity and engagement at work. The gathered data was analysed to determine the impact of the company’s individual talent management practices on the mediating variables ability, motivation and opportunity and finally on talent engagement. An indirect but no direct relationship between talent management and talent engagement was found in the investigated company. Deriving from the findings, this study recommends improving the talent management to positively influence the talents’ engagement and suggests the necessary subsequent steps on the path to improvement. Furthermore, the study provides a basis for further research regarding the analysed variables in the investigated company.